Pelatihan, Upah, Insentif, dan Masa Kerja terhadap Produktivitas Kerja Karyawan - Rina Anggraini; Rusdiana Simamora (Journal of Management and Bussines (JOMB), 2023)
The research aims to explain the effect of training, wages, incentives and years of service and work productivity at PT. Prosperous Star Plastindo. This research uses nonprobability sampling method. The respondents of this research were all employees at PT. Makmur Bintang Plastindo with a total of 145 employees. The instrument uses a questionnaire to collect data on training, wages, incentives and years of service, as well as work productivity variables. Data will be analyzed with multiple linear correlation coefficient tests, T tests, F tests, and calculation of the coefficient of determination. The results showed that the training variable on work productivity has a t count > t table or 3,150 > 1,976, and a significance of 0.002 <0.05; b) the wage variable on work productivity has a t count > t table or 4,521 > 1,976, and a significance of 0.000 <0.05; c) the incentive variable on work productivity has a t count > t table or 2,275 > 1,976, and a significance of 0.024 <0.05; d) the variable of years of service on work productivity has a value of t count > t table or 4,490 > 1,976, and a significance of 0.000 <0.05. The contribution of training, wages, incentives and years of service is 33.9% to increase work productivity. In conclusion, descriptive analysis for training, wages, incentives and years of service, as well as work productivity variables are in the good category at PT. Prosperous Star Plastindo. Furthermore, based on a partial analysis of training, wages, incentives and years of service, as well as work productivity variables positively and significantly affect the work productivity of employees at PT. Prosperous Star Plastindo. Simultaneously training, wages, incentives and years of service, as well as work productivity variables positively and significantly affect work productivity at PT. Prosperous Star Plastindo. Keywords: Incentives, Tenure, Training, Productivity, Wages